REPURCHASE INTENTION DITINJAU DARI BRAND IMAGE, BRAND TRUST DAN LIFESTYLE (STUDI KASUS PADA PRODUK NEVADA DI SURAKARTA) - Aloysia Syafa Kusumasari (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2020)
ABSTRACTThe purpose of this study was to determine the effect of brand image, brand trust, and lifestyle on repurchase intention of Nevada products in Surakarta. This type of research uses quantitative descriptive research. The population in this study were all consumers who had bought Nevada products more than twice. The sample of the study was 100 responden using purposive sampling technique. Methods of data using a questionnaire. The data analysis technique used in this study was multiple linear regression analysis technique. The conclusion of6this study is that brand image has a significant effect on repurchase intention, brand trust and lifestyle have no significant effect on repurchase intention.